Halophilic Archaea Halorhabdus Rudnickae and Natrinema Salaciae Activate Human Dendritic Cells and Orient T Helper Cell Responses - Krawczyk, Krzysztof T.; Locht, Camille; Kowalewicz-Kulbat, Magdalena (Frontiers in Immunology, 2022)
Halophilic archaea are procaryotic organisms distinct from bacteria, known to thrive in hypersaline environments, including salt lakes, salterns, brines and salty food. They have also been identified in the human microbiome. The biological significance of halophiles for human health has rarely been examined. The interactions between halophilic archaea and human dendritic cells (DCs) and T cells have not been identified so far. Here, we show for the first time that the halophilic archaea Halorhabdus rudnickae and Natrinema salaciae activate human monocyte-derived DCs, (MoDCs) induce DC maturation, cytokine production and autologous T cell activation. In vitro both strains induced DC up-regulation of the cell-surface receptors CD86, CD80 and CD83, and cytokine production, including IL-12p40, IL-10 and TNF-, but not IL-23 and IL-12p70. Furthermore, autologous CD4+ T cells produced significantly higher amounts of IFN- and IL-13, but not IL-17A when co-cultured with halophile-stimulated DCs in comparison to T cells co-cultured with unstimulated MoDCs. IFN- was almost exclusively produced by naïve T cells, while IL-13 was produced by both naïve and memory CD4+ T cells. Our findings thus show that halophilic archaea are recognized by human DCs and are able to induce a balanced cytokine response. The immunomodulatory functions of halophilic archaea and their potential ability to re-establish the immune balance may perhaps participate in the beneficial effects of halotherapies.